The robots of dawn - Asimov, Isaac 1920-1992 (A del rey book, 1983)
Presents readings from the third novel in a trilogy centering on the exploits of Lije Baley, a detective, at a time when earthlings have settled fifty other worlds. Focuses on the interplay between Lije and a woman named Gladia, and between Lije and the robots of the planet Aurora, where Lije is investigating the destruction of a robot.